From family solidarity to social classes: urban stratification in Angola (Luanda and Ondjiva) - Rodrigues, C. (Journal of Southern African Studies, 2007)
The analysis of recent social transformations in two Angolan cities – Luanda and Ondjiva – highlights the maintenance and strengthening of groups and social networks based on family ties on the one hand and, on the other, the construction of new solidarities and identities derived from a traditional framework and recreated in the urban context in recent decades. Family solidarity and reciprocity in the post-independence, post-war context in Luanda and Ondjiva are the basis of social strategies, and the new forms of urban extended family have supported individuals during rapid urban growth and socio-economic uncertainty in multiple ways: providing economic support, a main point for social reference and security, among other things. In Luanda this organisation has generated an atomised social structure, and in Ondjiva the urban social tissue that was completely erased during invasion and war relied for many years on rural solidarity ties. However, with the gradual yet massive migration towards the capital city, the return of displaced populations and the arrival of new migrants in Ondjiva, newer, broader and more complex forms of solidarity and social identity have emerged in recent years. The increasing complexity, along with the decrease in the capacity to sustain reciprocity and dependency networks, tends to lead to the formation of clearer social strata and the preponderance of new criteria. Both in Luanda and in Ondjiva, the urban reference – the integration, adoption and practice of an urban/modern lifestyle – together with the consolidation of a market economy and economic stratification, generates new social differentiation and tends to produce different layers within the urban population. In both urban centres, urban/cosmopolitan references tend to assume a central role in the formation of social differentiation, producing new forms of social identity and social status.